Pengaruh Illness Perception Terhadap Fungsi Paru Pasien Asma Rawat Jalan - Amelia Lorensia; Rivan Virlando Suryadinata; M Budi Indra Sudaryatmono (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: Illness perception is one of the factors of self-management, which can affect the outcome of asthmatreatment. Pulmonary function is more objective than clinical symptoms in asthma monitoring. Aim of study: Thepurpose of this study was to determine the effect of illness perception on lung function in outpatient asthmapatients. Method: The design that will be used in this study is the observational method. This research wasconducted in November 2018-January 2019. The independent variable used in this study was Illness perception ,while the dependent variable was lung function by measuring the FEV1 / FVC ratio using data collection techniqueswith a questionnaire to measure respondents' perception of illness and measurement of lung function withspirometry. Data analysis in this study used the chi-square test to determine the effect of illness perception on lungfunction values. This study involved 40 people, consisting of 5 respondents with disorders and 35 without lungfunction disorders. Results and Discussion: Illness perception based on asthma symptoms for symptoms ofshortness of breath affects lung function. Respondent's pain perception about identity, consequences, personalcontrol, treatment control, cyclical timeline, emotion, causal representation is correct, where the respondent knowsthe real symptoms experienced by asthmatics. As for the Illness coherence, and the timeline is still lacking, whererespondents do not know the real cause of asthma, uncontrolled asthma suffered because respondents said theywere doubtful or suddenly their asthma appeared besides that many respondents did not know that asthma would beexperienced for a lifetime. Conclusion: Therefore, in monitoring asthma treatment, we must pay attention to illnessperception because it can also affect the lung function of asthma patients.